A defesa heterotópica na execução de títulos executivos extrajudiciais no processo civil - Azevedo, Amanda Segato Machado de (2025)
Object: This research analyzes the autonomous action as a debtor's reaction to an extrajudicial executory title, known as "heterotopic defense," within the scope of civil procedure. It examines the relationships established between the execution, the heterotopic defense, and the motions to stay enforcements, aiming to establish the parameters and requirements of the heterotopic defense for discussing matters of the execution process. Issue: The repercussions of the heterotopic defense regarding the execution of an extrajudicial executory title and the execution-related claims are not yet uniform. This is because there is no specific legal regulation regarding the timing and matters that can be raised in this autonomous action. Its occurrence is only indirectly mentioned in Article 784, § 1, and Article 55, § 2, both of the Brazilian Code of Civil Procedure. Problem: What are the admissibility requirements for the heterotopic defense to discuss matters of the execution process, considering the legal provision for execution-related claims? Methodology: The research comprises a qualitative documentary analysis of legal literature, the Brazilian Codes of Civil Procedure of 1973 and 2015, and judgments from the Superior Court of Justice. To this end, the deductive method was employed, starting from general premises, considered true, towards singular premises, to propose the admissibility requirements for the use of the heterotopic defense. Results: The delimitation of the timing and cognizable matters in the heterotopic defense, in contrast to unoffered execution-related claims, based on Article 784, § 1 of the Code of Civil Procedure. Contributions: The research demonstrates that filing an autonomous action after the deadline for execution-related claims has passed without them being filed, raising defense matters that should have been presented therein, may seem to compromise the purpose of the execution related claims. However, the legislator did not establish execution-related claims as the sole form of defense but merely as one of the avenues, a fact observed in legal literature. Furthermore, it develops a propositional thesis to structure the requirements, encompassing the procedural moment, the content of the allegations, and the connection with the unobjected execution, aiming to provide, at this point, clarity and applicability to Article 784, § 1 of the CPC. From a practical standpoint, the research shows that although execution-related claims are the typical means for the debtor to defend against the execution of an executory title, the debtor is allowed to choose other procedural avenues, albeit with distinct legal consequences for each type of defense. From a social perspective, it contributes to the fair and effective delivery of judicial services, ensuring both the creditor's right to the satisfaction of their claim and the debtor's possibility of challenging an unjust execution, while also providing sanctions for dilatory conduct and conduct inconsistent with the principles of procedural good faith